A Feasibility Study on the Use of the Method of Loci for Improving Episodic Memory Performance in Schizophrenia and Non-clinical Subjects - Sousa, Ana Elisa; Mahdid, Yacine; Brodeur, Mathieu; Lepage, Martin (Frontiers in Psychology, 2021)
We investigated the feasibility of a short intervention using the Method of Loci (MoL), a well-known visuospatial mnemonic, to improve episodic memory recall performance in schizophrenia. The MoL training protocol comprised encoding and recall of two lists of items (words and images), a training session and practice with MoL. Then, participants had the opportunity to put into practice the newly learned MoL and were instructed to encode and recall two new lists of items using. This approach was first validated with healthy individuals (N = 71). Subsequently, five individuals with schizophrenia completed the protocol. Improvement in healthy individuals was observed for the word list (Wilcoxon effect size r = 0.15). No significant memory improvement was denoted in the schizophrenia group, possibly due to participants’ difficulties using the method efficiently and due to fatigue. The MoL seems to require episodic memory, working memory monitoring and executive functions, making it suboptimal for a population with impairments in all those domains. Future research should examine the use of other strategies, better suited for individuals with cognitive impairments like those found in schizophrenia.